Wise Saying – Aphorism and Proverb (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article discusses the interrelation between folk proverbs and aphorisms, the influence of oral creativity on written literature, and the principles by which the wise sayings of representatives of written literature turn into folk proverbs. Folk proverbs, in fact, were once uttered by a certain individual, but over time they adapted to the people’s taste and way of life and became folklore samples. The author of the expressed idea is forgotten. Folklore usually develops by constantly drawing nourishment from written literature; in particular, the edifying thoughts of great thinkers, poets, and statesmen create a broad foundation for the expansion of folk proverbs. The article puts forward scholarly views precisely on this issue.